Study on motion analysis and force/position hydraulic control of a parallel cylinder transmission system of heavy-duty quadruped robot. (25th February 2019) - Shao, Junpeng; Jin, Chaohui; Wang, Xigui; Wang, Yongmei; Jing, Jing; Zhou, Xue
In the article, a heavy-duty quadruped robot was designed. A parallel cylinder transmission scheme for the heavy load torque of the hip joint of heavy-duty hydraulic quadruped robot is proposed, the mathematical model of the parallel cylinder system is derived, the model characteristics of the parallel cylinder system are analyzed, the characteristics of internal force and joint control of parallel cylinders are considered, the force/position hybrid control of parallel cylinder is proposed to eliminate the internal forces and realize the requirement of joint control and the force/position control is decoupled by the design of the force and position signal. According to the characteristics of the servo cylinder force control model, the flow compensation and speed compensation are introduced, the minimum control synthesis controller is used to control the servo cylinder force and the proportional integral controller is applied to control the position of servo cylinder. The compound control strategy is analyzed on the table of parallel cylinder, and the experimental results show that the amplitude attenuation and phase lag of position and force are less than 10% and 18°, respectively, and the efficiency of the proposed control strategy is verified. The research results of this article will be widely used in many fields of robot control in the future.